2019
DOI: 10.1002/adma.201901640
|View full text |Cite
|
Sign up to set email alerts
|

High‐Lithium‐Affinity Chemically Exfoliated 2D Covalent Organic Frameworks

Abstract: Covalent organic frameworks (COFs) with reversible redox behaviors are potential electrode materials for lithium‐ion batteries (LIBs). However, the sluggish lithium diffusion kinetics, poor electronic conductivity, low reversible capacities, and poor rate performance for most reported COF materials limit their further application. Herein, a new 2D COF (TFPB‐COF) with six unsaturated benzene rings per repeating unit and ordered mesoporous pores (≈2.1 nm) is designed. A chemical stripping strategy is developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
247
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 51 publications
5
247
0
Order By: Relevance
“…Although Tsuru and co‐workers demonstrated that thin films can be prepared from a dilute suspension (0.15 mg mL −1 ) of COF‐1 powder prepared through sonication in dichloromethane, the fabrication process required repeated drop‐casting/drying cycles to form a continuous film, and therefore lacks scalability and practicality . More recently, charge‐mediated and chemical exfoliation strategies have been developed, which produce more concentrated suspensions (≥0.5 mg mL −1 ) that can be drop‐cast to produce large‐area films . However, these strategies have thus far made use of intentionally incorporated functional groups that are not generalizable across broad classes of COF networks .…”
Section: Introductionmentioning
confidence: 99%
“…Although Tsuru and co‐workers demonstrated that thin films can be prepared from a dilute suspension (0.15 mg mL −1 ) of COF‐1 powder prepared through sonication in dichloromethane, the fabrication process required repeated drop‐casting/drying cycles to form a continuous film, and therefore lacks scalability and practicality . More recently, charge‐mediated and chemical exfoliation strategies have been developed, which produce more concentrated suspensions (≥0.5 mg mL −1 ) that can be drop‐cast to produce large‐area films . However, these strategies have thus far made use of intentionally incorporated functional groups that are not generalizable across broad classes of COF networks .…”
Section: Introductionmentioning
confidence: 99%
“…S4b †), it is easy to nd a weak peak appearing at 289.8 eV, which corresponds to the C-Li groups and can be ascribed to the lithiation reaction with C]C groups. 20 Therefore, lithium storage in Ni-CAT mainly relies on the reversible insertion/de-insertion in its organic ligands and pores (Fig. S5, ESI †).…”
mentioning
confidence: 99%
“…This is due to their strong covalent framework with open channels in π conjugate porous structure, which is used for reversible and smooth electrochemical insertion/extraction of Na ions. Chen et al. successfully exfoliated layered TFPB‐COF with the method of chemical exfoliation and obtained TFPB‐COF (E‐TFPBCOF) and E‐TFPB‐COF/MnO 2 composite nanosheets (Figure a).…”
Section: Electrochemical Applications Of 2d Mof/cof Nanosheetsmentioning
confidence: 99%